The "Sausage" and "Toothbrush" clusters of galaxies and the prospects of LOFAR observations of clusters of galaxies. Issue 4 (2nd May 2013) - Röttgering, H.; van Weeren, R.; Brüggen, M.; Croston, J.; Hoeft, M.; Ogrean, G.; Barthel, P.; Best, P.; Bonafede, A.; Brunetti, G.; Cassano, R.; Chyży, K.; et al.
Abstract LOFAR, the Low Frequency Radio Array, is a new pan‐European radio telescope that is almost fully operational. One of its main drivers is to make deep images of the low frequency radio sky. To be able to do this a number of challenges need to be addressed. These include the high data rates, removal of radio frequency interference, calibration of the beams and correcting for the corrupting influence of the ionosphere. One of the key science goals is to study merger shocks, particle acceleration mechanisms and the structure of magnetic fields in nearby and distant merging clusters. Recent studies with the GMRT and WSRT radio telescopes of the "Sausage" and the "Toothbrush" clusters have given a very good demonstration of the power of radio observations to study merging clusters. Recently we discovered that both clusters contain relic and halo sources, large diffuse regions of radio emission not associated with individual galaxies. The 2 Mpc northern relic in the Sausage cluster displays highly aligned magnetic fields and and exhibits a strong spectral index gradient that is a consequence of cooling of the synchrotron emitting particles in the post‐shock region. We have argued that these observations provide strong evidence that shocks in merging clusters are capable of accelerating particles. For the Toothbrush cluster we observe a puzzling linear relic that extends over 2 Mpc. The proposed scenario is that a triplemerger can lead to such a structure. With LOFAR's sensitivity it will not only be possible to trace much weaker shocks, but also to study those shocks due to merging clusters up to redshifts of at least one. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)